Motivations and Experiences of Volunteering Medical Students in the COVID-19 Pandemic—Results of a Survey in Germany - Büssing, Arndt; Lindeberg, Alexander; Stock-Schröer, Beate; Martin, David; Scheffer, Christian; Bachmann, Hagen S. (Frontiers in Psychiatry, 2022)
Introduction: During the first lockdown of the COVID-19 pandemic, several medical students volunteered as assistants in hospitals, public health departments and other health care services to support and substitute permanent staff. The underlying motivations to help are unclear. Therefore, we aimed to assess medical students´ motivations and influencing variables such as perceived stress and burden, compassion, and indicators of spirituality. Materials and Methods: Cross-sectional survey (convenience sample) from May to June 2020, directly after the first lockdown, among medical students with standardized instruments. One of them is the 12-item Motivations to Help Scale (MtHS), designed to fit to the population of medical students. Results: Among the 731 completers, 52% were working as volunteers during the pandemic in different medical areas, most in hospitals and only a few in other areas (9% in public health departments, 6% in outpatient services, 37% would have liked to work but did not get an appropriate employment, and 21% did not intend to voluntarily support the hospital staff. Their mental burden during work was rather low, while they were somewhat affected by the personal fate of the patients. With respect to their motivations to volunteer as measured with the MtHS, Altruistic Intentions / Helping (Cronbach´s alpha = .898) scored highest, followed by Practical Application / Learning (Cronbach´s alpha = .808), while Role Testing / Recognition (Cronbach´s alpha = .702) scored lowest. Those who volunteered had significantly higher scores for Altruistic Intentions / Helping and Practical Application / Learning, while the different phases of medical study (preclinical phase, clinical phase and higher semester) had no influence on the extent of the students´ motivation. The motivations to help were not at all or only marginally (inversely) related to indicators of stress and burden, while Altruistic Intentions / Helping was weakly related to affections by patients´ fate. Conclusions: Medical students´ intention to support health care professionals as supplementary assistants were both, prosocial and proself motivated. With this opportunity to practically apply their current knowledge and to improve their skills and competences, volunteering students might be more motivated for their further studies and future career as compassionate medical doctors.